How does the quality of life and the underlying biochemical indicators correlate with the performance in academic examinations in a group of medical students of Sri Lanka? - Manjula Hettiarachchi; Chathuranga Lakmal Fonseka; Priyanka Gunasekara; Prasanjanie Jayasinghe; Dasun Maduranga (Medical Education Online, 2014)
Background: Individual variation of examination performance depends on many modifiable and non-modifiable factors, including pre-examination anxiety. Medical students’ quality of life (QoL) and certain biochemical changes occurring while they are preparing for examinations has not been explored. Purpose: We hypothesize that these parameters would determine the examination performance among medical students. Methods: Fourth-year medical students (n=78) from the University of Ruhuna, Sri Lanka, were invited. Their pre- and post-exam status of QoL, using the World Health Organization Quality of Life (WHOQOL-BREF) questionnaire, and the level of biochemical marker levels (i.e., serum levels of thyroid profile including thyroglobulin, cortisol and ferritin) were assessed. Differences between the scores of QoL and serum parameters were compared with their performance at the examination. Results: The mean QoL score was significantly lower at pre-exam (56.19±8.1) when compared with post-exam (61.7±7.1) levels (p<0.001). The median serum TSH level prior to the exam (0.9 mIU/L; interquartile range 0.74–1.4 mIU/L) was significantly lower (p=0.001) when compared with the level after the exam (median of 2.7 mIU/L; IQR 1.90–3.60). The mean±SD fT4 level was significantly higher before the exam (19.48±0.4 pmol/L at study entry vs. 17.43±0.3 pmol/L after the exam; p<0.001). Median serum ferritin (SF) level prior to the exam (43.15 (23.5–63.3) µg/L) was significantly lower (p≤0.001) when compared with after-exam status (72.36 (49.9–94.9) µg/L). However, there was no difference in mean serum cortisol levels (16.51±0.7 at pre-exam and 15.88±0.7 at post-exam, respectively; p=0.41). Conclusions: Students had higher fT4 and low ferritin levels on pre-exam biochemical assessment. It was evident that students who perform better at the examination had significantly higher QoL scores at each domain tested through the questionnaire (Physical health, Psychological, Social interaction and Environment). The higher the QoL scores, the better the grades were. It was also found that students who failed exhibited profound differences in the QoL score.